Biodiver-cidade: vivendo e experimentando o espaço urbano na educação ambiental para e com a biodiversidade - Hofstatter, Lakshmi Juliane Vallim (2018)
In view the fact that most of the Brazilian population lives in urban centers and an increasing indication of a greater development of environmental education in cities, this research aims to better understand the forms and spaces for the realization of experiences and learning practices with and for biodiversity, in Salvador- BA city. Thus, in the first moment, I analyze a formative process for tracks guides in relation to the theme of urban biodiversity and, later, the visitation process of a trail implemented at the Federal University of Bahia (UFBA). We sought to understand the contents and sensory experiences that were significant during this experience. Twenty-six undergraduate students from UFBA and 77 trail visitors, also UFBA students, as well as students from secondary schools in Salvador were involved. Data were obtained through questionnaires and interviews. In a second moment of the research, I tried to investigate in what ways people Interact to the urban space and what are the childhood memories and the lived ways in the affective ties development to the urban nature. At that time, 18 university students participated, and among these, there was a more intense work with 9 people, with whom I toured, individually, city places considered affective by themselves. Thus, this research starts from a phenomenological perspective and continues the postmodern studies of the new materialism. For this, we also try out more recent methodologies of mobiles studies, such as walking interview. This work evidenced that the knowledge process happens from a relational and multisensory body, which in movement, in affection, in space and in relations with other beings and things, weaves its learning in this mesh of so many threads. It was possible to understand the need for investment in the sensorial and sensitizing aspects of educational content. We observe that there is a web of human and nonhuman relations in the city, created in the urban nature, in which we perceive how much people maintain ties to the other environmental links being / living in this environment. In revisiting people's memories, it was possible to perceive the importance of these places in the connection that these people have to/in the world, since the coexistence from childhood in the natural environments in the city influenced their life choices. We thus highlight the need to offer urban green areas accessible to the entire population; the educational potential of the city as a whole; and the working possibility with memories in educational practices and experiences as a subsidy to self-knowledge and a (re) connection with other beings and the urban environment.